PENGUATAN EKONOMI INDUSTRI KECIL DAN MENENGAH MELALUI PLATFORM KLASTER INDUSTRI - Lestari, Etty Puji (Jurnal Organisasi dan Manajemen, 2010)
The development of industry cluster and business network is believed to be able to improve the ability and competitiveness for small and medium enterprises (Industri Kecil dan Menengah/ IKM) because it can cope with IKM limitation to catch the chance of market share which needs high output production, homogenity standard and regular production. The facts in many countries show how the comparative advantages have shifted from natural based economy and low cost of work force to knowledge based economy. Thus, the ability of IKM to create, access and comercialize new knowledge to global market will determine continual competitiveness.